Subcutaneously anchored securement for peripherally inserted central catheters: Immediate, early, and late complications. Issue 1 (January 2023) - Brescia, Fabrizio; Pittiruti, Mauro; Roveredo, Laura; Zanier, Chiara; Morabito, Antonietta; Santarossa, Elisabetta; Da Ros, Valentina; Montico, Marcella; Fabiani, Fabio
Background: An adequate stabilization of a vascular device is an important part of insertion bundles and is an effective strategy in reducing complications. Dislodgment has a relevant clinical impact and an increase in healthcare costs. Method: We have retrospectively investigated the safety and efficacy of Subcutaneously Anchored Securement (SAS) for Peripherally Inserted Central Catheters (PICC) in cancer patients. Results: We analyzed 639 patients who had a PICC inserted and secured with SAS, over the past 3 years (2018–2020). No immediate complications during SAS placement were reported. In the first 24–48 h, a slight local ecchymosis was reported in 24 cases with rapid spontaneous resolution. No cases of bleeding or hematoma of the exit site were reported. The total number of catheter days was 93078. Dislodgment occurred only in seven cases (1.1%). In 16 patients, the PICC was removed because of catheter-related bloodstream infection (CRBSI): the overall incidence of CRBSI was 0.17 per 1000 catheter days. Symptomatic venous thrombosis was documented in 12 patients (1.9%) and treated with low molecular weight heparin without PICC removal. We had no cases of irreversible lumen occlusion. In 17 patients, local discomfort—including device-related pressure ulcers and painful inflammation—was reported: these cases were treated without SAS removal or PICC removal. Conclusion: In this retrospective analysis, subcutaneously anchored securement of PICCs was a safe and effective strategy for reducing the risk of dislodgment.